Autoantibody-associated psychiatric syndromes: a systematic literature review resulting in 145 cases - Endres, D; Maier, V; Leypoldt, F; Wandinger, K-P; Lennox, B; Pollak, TA; Nickel, K; Maier, S; Feige, B; Domschke, K; Prüss, H; Bechter, K; et al. (Cambridge University Press, 2020)
Background Autoimmune encephalitis (AE) is an important consideration during the diagnostic work-up of secondary mental disorders. Indeed, isolated psychiatric syndromes have been described in case reports of patients with underlying AE. Therefore, the authors performed a systematic literature review of published cases with AE that have predominant psychiatric/neurocognitive manifestations. The aim of this paper is to present the clinical characteristics of these patients.